A comparative study of moxifloxacin versus combination of doxycycline and metronidazole for treatment of uncomplicated pelvic inflammatory disease - M., Priyadharshini; Nath, Sarmila; Kamilya, Gourisankar; Roy, Raja (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Pelvic inflammatory disease (PID), a common condition among women of reproductive age caused by various aerobic and anaerobic organisms, may sometimes lead to complications like infertility, ectopic pregnancy and chronic pelvic pain. Moxifloxacin is a broad spectrum bactericidal antibiotic acting against many gram positive, gram negative aerobic organisms and anaerobes. Rapid absorption and high bioavailability allow single daily dosing and improves compliance. The present study was done to compare the clinical and microbiological outcomes in PID patients treated with conventional doxycycline- metronidazole and moxifloxacin therapy. Methods: Women with uncomplicated PID, randomized into two groups either received 400 mg single dose of moxifloxacin daily for 14 days (group A) or doxycycline 100 mg + metronidazole 500 mg twice daily for 14 days (group B). Temperature, TLC count, ESR, CRP, microbiological assessment, Visual analogue score for pain, vaginal discharge, dyspareunia and backache were noted. The bacteriological cure was assessed by high vaginal swab for organism identification by gram stain, 10% KOH and blood sample by ELISA. Results: Total 60 women were enrolled and randomized into two groups. There was significant reduction of CRP and improved TLC in the moxifloxacin treated group. Visual analogue scores for pain, vaginal discharge and malaise were significantly reduced in the group treated with moxifloxacin. Nausea, vomiting, metallic taste, dyspepsia and diarrhoea were complained by a significant number of patients of doxycycline + metronidazole group, in contrast to the patients receiving moxifloxacin. Conclusions: Moxifloxacin 400 mg once daily, is effective and safe for treatment of PID.